To be fair, generous, or selfish: The effect of relationship on Chinese children's distributive allocation and procedural application. Issue 2 (10th October 2018) - Li, Weiwei; Curtis, Robin; Moore, Chris; Wang, Yun; Zeng, Xihua
Abstract: Previous research has found that children's sharing with others relies on fairness norms, but also varies according to their social relationships. The current study focuses on the conflict between fairness and relationship, exploring their impacts across two resource allocation contexts. We used a parallel work task to explore the effect of relationship with different recipients (friend, stranger, or disliked peer) on three allocation patterns (generous, fair, or selfish), when children directly allocated resources (distributive allocation), or applied different procedures to recipients (procedural application). Participants consisted of 123 Chinese children between the ages of 6 and 12. We found that in the distributive allocation context, in which participants directly decided the outcome, children primarily considered their relationship with recipients when dividing resources, not fairness. However, in the procedural application context, in which children could choose different allocation procedures for recipients, children primarily preferred fairness, regardless of social relationship. Moreover, when making distributive allocations, 6‐ to 8‐year‐olds were more selfish toward their disliked peers, whereas 9‐ to 12‐year‐olds tended to be more fair and generous toward their friends and strangers. These findings shed light on the link between social relationship and fairness within different allocation contexts among children of Chinese cultural background.